“Pakistan’s Scenario in Pandemic Situation of COVID-19” - Saima Mazhar; Farzeen Tanwir (Journal of Bahria University Medical and Dental College)
Emergence of Covid-19 in Pakistan is an element of continuing pandemic caused by (SARS-CoV-2) virus1.It was confirmed in our country on 26th February 20202. By 18th March 2020, cases were confirmed in 4 different provinces of Pakistan,3 and by 17th June, each district had recorded a minimum of one confirmed case of COVID-19